The epistemological construction in Civil Engineering: the vision of the University of Costa Rica - Cruz Zúñiga, Nidia (2019)
Defining the scope of a discipline is indispensable for its academic and pedagogical development. For the civil engineering in Costa Rica, there is no precedent for this task in the past. This article aims to synthetize the process of construction of an epistemological frame for Civil Engineering in Costa Rica, as part of an updating process for the graduate profile for civil engineer students at the University of Costa Rica.  A qualitative and quantitative approach; along with a participative observation within a teacher commission integrated by 14 people that was created in the Civil Engineer School specifically for that purpose. Queries through interviews, workshops and inquiries were applied to stakeholders. The samples were composed of teachers (74), researchers (10), featured professionals (10), students (278), graduates (1506) and employers (306). The answers of each population were compared and completed with international references. The main results of this research are a definition, adapted to the local context, of key concepts for establishing an epistemology for civil engineering: engineering, civil engineering and its specialties. In addition, historical transformations on how the formation is taught and how it is learnt were identified. Finally, some changes derived from the current technological revolution that would complement the traditional vision of the discipline were identified.